2012
DOI: 10.1016/j.aat.2012.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity reaction probably induced by sugammadex

Abstract: We report here an intellectually compromised 7-year-old boy with cerebral palsy who developed a hypersensitivity reaction several minutes after the administration of sugammadex for subsequent extubation. He developed signs of upper airway stenosis and decreased oxygen saturation, as well as wheals on his neck, chest, and both upper extremities. He was successfully treated with immediate administration of adrenaline and hydrocortisone. A hypersensitivity reaction to sugammadex was suspected on the basis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Some other studies reported hypersensitivity and anaphlaxis during sugammadex use [18][19][20][21] . In addition, a bitter taste and coughing due to the high dose of the drug were also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies reported hypersensitivity and anaphlaxis during sugammadex use [18][19][20][21] . In addition, a bitter taste and coughing due to the high dose of the drug were also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports described sugammadex‐induced anaphylactic reactions in adults . A previous study reported that incidence proportion of sugammadex‐induced anaphylactic reactions was estimated to be 0.003% .…”
Section: Introductionmentioning
confidence: 99%
“…However, the data were obtained from anesthesiologists on a voluntary basis, and may have been underreported. Regarding pediatric patients, only a few small studies have reported anaphylaxis after sugammadex administration …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations